MELAWAN EXTRAODINARY CRIME BERNAMA PLAGIARISME : SEBUAH BINGKAI DI LIPUTAN UTAMA TEMPO - Christopher Chandra; Theresia Intan Putri Hartiana; Nanang Krisdinanto (Universitas Muhammadiyah Jember, 2022)
The mass media holds an important element in aspects of public life, because of the power of mass media itself which can provide information and form public opinion, through the published news. Making news in the mass media is essentially a compilation of the realities seen by journalists wbich are then rearranged to form a new “story”. Therefore, it is not an exaggeration to say that all media content is a constructed reality. Media coverage is an effort to construct reality, which is an effort to restructure the reality of an event or a number of events that were originally fragmented (random) to become systematic to form a meaningful story or discourse. Because the way to construct an event will give a certain image of reality. One of the aspects of public life is the world of higher education, especially in Indonesia. Where it is important to know how the mass media provide a picture or portrait of higher education, which of course will be able to provide a perspective on the quality of education in Indonesia. Plagiarism is one of the issues that has received sharp attention regarding to the quality of education in Indonesia. Tempo specifically provides coverage related to plagiarism by leaders of the world of higher education. Kasus plagiarisme merupakan kasus yang seringkali terjadi di Pendidikan Tinggi di Indonesia terutama di kalangan akademisi. Berdasarkan fenomena tersebut, tidak berlebihan jika disebutkan bahwa penghargaan karya ilmiah orang lain belum dianggap sebagai sesuatu yang penting. Selain itu, rendahnya rasa penghargaan terhadap karya penulis juga menjadi hal yang belum diperhatikan dalam penulisan karya ilmiah. Berdasarkan fenomena tersebut, penelitian tersebut akan mendeskripsikan penonjolan berita pada berita plagiarism di lingkungan perguruan tinggi. Penelitian ini menunjukkan bahwa badan penulisan ilmiah seperti lingkungan pendidikan tinggi masih melindungi dan memfasilitasi para pelaku untuk menjiplak karya orang lain dan kurangnya sikap tegas dari pemerintah dalam menyoroti kasus plagiarisme.